Development of a dynamic compositional reservoir model for enhanced oil recovery in Nahr Umr formation of Abu-Amood oil field - Abed Talib, Mohammed Q.; Al-Jawad, Mohammed S. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Due to the research gap in the literature regarding the Nahr Umr formation within the Abu-Amood oil field, this study aims to develop a dynamic compositional reservoir model for this formation. Located in the Dhi Qar province of Iraq, the Nahr Umr Formation, primarily composed of sandstone, lies 3025 meters below sea level and holds significant hydrocarbon potential. This research focuses on building a compositional model to predict reservoir behavior under various production strategies, ultimately maximizing oil recovery. The model was constructed using geological report data and implemented with Petrel and CMG software. Utilizing pressure-volume-temperature (PVT) data and the Peng-Robinson equation of state (EOS), an accurate fluid properties model was developed. Through reservoir and well area calculations, this study demonstrates that the Nahr Umr reservoir can be effectively drained using only six producers. This comprehensive model is crucial for designing efficient production strategies and enhancing oil recovery in the Nahr Umr Formation.